PRICING BERMUDAN-TYPE CALL OPTION THROUGH BINOMIAL TREE METHOD - Izma Fahria (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
Bermudan option is a type of option that has characteristics between American option and European option whose its value never exceeds the value of the American option and is never less than the European option. The objective of this research is to calculate Bermudan call option of John Keels Stock through the binomial tree method using statistics software of Matlab R2010a. Assessment of Bermudan type option relates to discrete issues, in which the Bermudan type option has a certain number of times of early exercise specified in the option contract, where such times can only be made at some time prior to the option due date. Precise pricing for Bermudan type option can be obtained by discrete models such as the binomial tree method, a numerical method that is one of the most popular approaches for calculating option prices. This research uses time series data obtained from BNI Financial Update Corner, FEB UGM. The Bermudan call option price calculation will be compared with the calculation of European option pricing and American option price with underlying asset without dividend. The results show that the price of John Keels's Bermudan type call option using the binomial tree method yields the same value as American type call option and European type call option.Keywords: Bermudan Type Option, Binomial Tree Method, Matlab R2010a, Spss 20